(untitled) (Vietnam Journal of Community Medicine, 2025)
This scoping review summarized the classification of thyroid cancer diagnosis worldwide and in Vietnam in the period 2009 to 2019. A total of 8 guidelines worldwide and Vietnam were analyzed in this review, revealing that the cytological classification across these guidelines is largely consistent, including the following categories: non-diagnostic/unsatisfactory, benign, atypia of undetermined significance/follicular lesion of undetermined significance, suspicious for malignancy, and malignant. The reclassification of certain follicular variants of papillary thyroid carcinoma cases as non-invasive follicular thyroid neoplasm with papillary-like nuclear features has led to changes in treatment approaches, reducing the number of patients undergoing aggressive cancer therapies while better aligning with the benign prognosis of these lesions. The transition from AJCC 7 to AJCC 8 has had a significant impact on clinical practice, providing more accurate treatment guidance for thyroid cancer patients. Updating and integrating international guidelines into clinical practice is crucial in enhancing diagnostic accuracy, improving prognosis, and optimizing treatment quality for thyroid cancer patients.